Analisis Ketahanan Hidup Balita Penderita Stunting Menggunakan Model Cox Proportional Hazard - Amelia Puspita Anggraeni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Stunting is a health problem that describes the condition of failure to thrive in children under the age of age five due to chronic malnutrition especially in the first 1000 days of life (HPK), so that children are too short for their age. Many factors cause toddlers to experience stunting. Stunting conditions have a negative impact on children's academic achievement, because children with stunting conditions tend to have low learning achievement compared to children who do not experience stunting conditions. The purpose of this study was to determine what factors have the most influence on the incidence of stunting. This study uses the cox proportional hazard model to analyze the survival of toddlers with stunting. The results of this study obtained a cox proportional hazard model ℎ(𝑡)=ℎ). The most influential factor based on the results AIC model with the smallest value is gender, vitamin and mineral 0(𝑡)𝑒𝑥𝑝⁡ 1,7397𝑋1+ 2,5103𝑋8+ 1,7705𝑋9 administration, and 90-day PMT. Based on the results of the hazard ratio value, the results obtained for patients with female gender have a higher risk of death of 5,6955 than patients with male gender. Patients who were not given vitamins and minerals had a 12,3092 higher risk of death than patients who were given vitamins and minerals. Patients who were not given PMT had a 5,8736 higher risk of death than patients who were given PMT.
Entry oleh Arif 2026 Januari 29
Keywords: cox prportuonal hazard model; stunting; stunting factors